Characteristics of the environmental disclosure of potentially polluting Brazilian companies: Analysis of financial statements and sustainability reports for the period from 2005 to 2007 - Rover, Suliani; Borba, José Alonso; Murcia, Fernando Dal Ri (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This paper aims to identify characteristics of Brazilian companies’ voluntary environmental disclosure. The research was driven through an analysis of Standardized Financial Statements (SFSs) and Sustainability Reports (SR) from 2005 to 2007. The analyzed group is composed by Brazilian companies whose stocks are listed in Sao Paulo Stock Exchange (BOVESPA) and belong to the high environmental impact sector. The authors use the qualitative approach of Content Analysis to search and analyze parameters like “type of evidence”, “type of news”, “temporal reference” and “location of the disclosure”. It is concluded that the research corroborates the Voluntary Disclosure Theory, since companies voluntarily did not disclose much negative information about their environmental practices.